2001
DOI: 10.1111/1468-2397.00188
|View full text |Cite
|
Sign up to set email alerts
|

Migration, ageing and mental health: an ethnographic study on perceptions of life satisfaction, anxiety and depression in older Somali men in east London

Abstract: This ethnographic study was carried out in the aftermath of an epidemiological investigation, the first of its kind, on the health and social status of Somalis aged 60 years and over living in Tower Hamlets, east London. The main aims of the study are to explore views on mental health and well‐being and identify sources of stress and support so as to gain greater understanding of background factors of life satisfaction and depression in ‘first‐generation’ older Somali migrants in Tower Hamlets (males). Face‐to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 19 publications
3
79
2
1
Order By: Relevance
“…Rousseau et al (2004a) highlight the distinctive nature of family separation and reunification amongst refugee families: people feel guilty, powerless and depressed about separation from relatives who may be in difficult situations abroad; family roles are reconfigured; and it is challenging for reunified families to establish balance and redefine relationships. A number of other studies have identified that family separation is associated with depression, anxiety and somatisation (Lie 2002, Rousseau et al 2004b, Luster et al 2008 and is found to contribute significantly to long-term trauma (Gorst-Unsworth andGoldenberg 1998, Silveira andAllebeck 2001). In this study, participants spoke of longing to see family who remain overseas, ongoing worry about these relatives, provision of remittances and efforts to sponsor relatives through Australia's family reunion programme.…”
Section: Discussionmentioning
confidence: 84%
“…Rousseau et al (2004a) highlight the distinctive nature of family separation and reunification amongst refugee families: people feel guilty, powerless and depressed about separation from relatives who may be in difficult situations abroad; family roles are reconfigured; and it is challenging for reunified families to establish balance and redefine relationships. A number of other studies have identified that family separation is associated with depression, anxiety and somatisation (Lie 2002, Rousseau et al 2004b, Luster et al 2008 and is found to contribute significantly to long-term trauma (Gorst-Unsworth andGoldenberg 1998, Silveira andAllebeck 2001). In this study, participants spoke of longing to see family who remain overseas, ongoing worry about these relatives, provision of remittances and efforts to sponsor relatives through Australia's family reunion programme.…”
Section: Discussionmentioning
confidence: 84%
“…This group is markedly heterogeneous, not just in terms of origins and cultural and ethnic characteristics, but also in the extent to which they have raised children and formed social networks at the destination, important factors in their ability both to develop satisfying roles when no longer in work and, should their abilities decline, to turn to informal family and community support (Silveira and Allebeck 2001). There is also considerable diversity in their knowledge of, entitlements to and utilisation of the full range of state income, social housing, social service and health-care benefits and services.…”
Section: The Principal Groups Of Older Migrants and Their Migrationsmentioning
confidence: 99%
“…The first focused on migration, whereby people move within or between countries with implications for their health and health care systems (Boyle 2004;Norman et al 2005). The particular ageing focus here being longstanding on the migration destinations, motivations, decisions and experiences of older people and the implications for ageing services and policy (Wiseman et al, 1979;Warnes et al, 1984;Bentham, 1988;Joseph et al, 1991;Glaser et al, 1998;Silveira et al, 2001;Moore et al, 2004;Oliver, 2007). Indeed this research is not focused on the act of moving long distances per-se, as much as the shape, impact and consequence of the completed/past movements at the collective and macro scale.…”
Section: Current Engagements With Human Movements: Key Empirical Themesmentioning
confidence: 99%
“…1 引言 本文将非表征理论引入现有理论工具之中, 这 将是对当前老龄化地理学在概念、 理论和实证方面 的 有 益 补 充 (Andrews et al, 2007(Andrews et al, , 2009(Andrews et al, , 2013Golant, 2003;Hopkins et al, 2007;Skinner et al, 2015 (Boyle, 2004;Norman et al, 2005)。在此方面老龄化 研究的长期特别关注点是老年人的迁移目的地、 动 机、 决策过程和迁移经历, 以及对老龄化服务政策 的 影 响 (Wiseman et al, 1979;Warnes et al, 1984;Bentham, 1988;Joseph et al, 1991;Glaser et al, 1998;King et al, 2000;Silveira et al, 2001;Moore et al, 2004;Oliver, 2007)。事实上, 这些研究并不关注 长距离迁移行为本身, 而关注在总体和宏观尺度上 已经完成的(过去的)迁移活动的状况、 影响和结 果。近年来, 对时空尺度上人类生命历程所起作用 和迁移的批判性思考和研究已有所增加。这些研 收稿日期: 2015-12; 修订日期: 2015-12。 作者简介: Gavin J. ANDREWS, 男, 加拿大人, 副教授, 主要从事护理学和心理学的研究, E-mail: g.andrews@utoronto.ca。 第 12 期 Gavin J. ANDREWS 等:老年人移动构成的时空 究对生命的 "历程" 在微观尺度上的多次迁移和迁 移的意义更为敏感 (Bailey, 2009;Jarvis et al, 2011;Schwanen et al, 2012)。 (2) 基于体能活动的观点而迅速发展的新兴多 学 科 交 叉 研 究 (Witten et al, 2008;Matthews et al, 2009), 尤其是 "可步行性" 概念的提出及相关研究 已成为当前研究热点。例如, 该方面的研究已经特 别关注到可步行城市环境的营造和形式 (Ewing et al, 2009;Gehl, 2010 (3) 基于活动是健康的关联因素的认识, 探讨 健康和社会照护服务者与需求者之间的空间距 离。这些研究也归属健康地理学关于 "可达性及其 使用行为" 的研究领域 (Joseph et al, 1984); 通常强 调服务使用行为的距离衰减效应(随着距离的增 加, 对服务的使用频率下降), 及其对健康所产生的 影响。对老年人口相关的研究, 不仅考虑服务的使 用行为, 也关注 "非行动" 因素, 包括老年人住址与 服务设施、 居住距离较远的子女和其他照护者的邻 近度 (Joseph et al, 1998;Nemet et al, 2000) 此外, 在社会地理和健康地理的研究中, 另有 3 个研究领域通过以定性方法为主导的途径, 对人类 移动进行了更为直接和更具批判性的研究。第一 个领域主要关注损伤、 残疾及其相应情况下的移动 性, 以及受损个体因此所面临的挑战和社会接纳 (Butler et al, 1999;Gleeson, 1999;Crooks et al, 2008)。该领域的研究焦点在于老年人的移动空间 与范围 (Meyer et al, 1985;Schwanen et al, 2010)、 城 市和农村所面临的不同挑战 …”
unclassified